Conveyor Performance Analysis In Secondary Packaging Using the Time and Motion Study Method: Analisis Kinerja Conveyor pada Pengemasan Sekunder dengan Metode Time And Motion Study - Haiyul Fadhli; Ica Winanda Anggraeni; Whulan Mudia; Marshal M. Kamil (Universitas Muhammadiyah Purwokerto, 2026)
To avoid a shortage of drug stocks in the market with the high number of market demands, PT. Trifa Raya Laboratories always evaluates to achieve good product quality, one of which is in the field of packaging by optimizing the amount of labor and time needed using conveyor tools. The purpose of this study is to determine the optimal amount of manpower needs in the secondary packaging process at PT. Trifa Raya Laboratories using the Time and Motion Study method. This method was chosen to measure the time and efficiency of worker movements in each packaging activity, so that it can increase productivity. Data were collected through direct observation in the field with variations in the number of workers (5, 6, and 7 people) and were carried out three times every 5 minutes at different times. The results showed that the packaging of envelopes and small boxes was optimal with 7 workers, resulting in productivity per person of 21.33 and 52.24 respectively. Meanwhile, the packaging of medium and large boxes is optimal with 5 and 6 workers, resulting in productivity per person of 68.53 and 65.44 respectively. The conclusions of this study emphasize the importance of determining the ideal number of workers to increase efficiency and productivity in the secondary packaging process, as well as the need to pay attention to the level of complexity of packaging and the skills of workers. ABSTRAK (Bahasa Indonesia) Untuk menghindari kekosongan stok obat di pasaran dengan tinggi nya jumlah permintaan pasar, PT. Trifa Raya Laboratories selalu melakukan evaluasi untuk mencapai mutu produk yang baik salah satunya pada bidang pengemasan dengan mengoptimalkan jumlah tenaga kerja dan waktu yang dibutuhkan menggunakan alat conveyor. Tujuan dari penelitian ini untuk menentukan jumlah kebutuhan tenaga kerja yang optimal pada proses pengemasan sekunder di PT. Trifa Raya Laboratories dengan menggunakan metode Time and Motion Study. Metode ini dipilih untuk mengukur waktu dan efisiensi gerakan pekerja dalam setiap aktivitas pengemasan, sehingga dapat meningkatkan produktivitas. Data dikumpulkan melalui observasi langsung di lapangan dengan variasi jumlah pekerja (5, 6, dan 7 orang) dan dilakukan sebanyak tiga kali setiap 5 menit pada waktu yang berbeda. Hasil penelitian menunjukkan bahwa pengemasan dus amplop dan kecil optimal dengan 7 pekerja, menghasilkan produktivitas per orang masing-masing sebesar 21,33 dan 52,24. Sementara itu, pengemasan dus sedang dan besar optimal dengan 5 dan 6 pekerja, menghasilkan produktivitas per orang masing-masing sebesar 68,53 dan 65,44. Kesimpulan dari penelitian ini menekankan pentingnya penentuan jumlah tenaga kerja yang ideal untuk meningkatkan efisiensi dan produktivitas dalam proses pengemasan sekunder, serta perlunya perhatian terhadap tingkat kerumitan pengemasan dan keterampilan pekerja.